Genetic diversity affects seedling survival but not growth or seed germination in the Bornean endemic dipterocarp Parashorea tomentella - Nutt, Kirsty S.; Burslem, David F. R. P.; Colin Ruzelion Maycock; Ghazoul, Jaboury; Khoo, Eyen; Alexander Y. L. Hastie; Kettle, Chris J. (Taylor and Francis, 2016)
Background: Logging and habitat fragmentation of tropical rain forests may disrupt patterns of gene flow and genetic diversity. Consequently, inbreeding in tree populations may reduce fitness and increase extinction risks, especially among species that are predominantly outcrossing, dependent on biotic pollination and/or display limited seed dispersal such as species of the Dipterocarpaceae.